Fragility Assessment of Cable-Stayed Bridge Towers Under Scaled Earthquakes - Mamdouh, Nouran; Attia, Walid A.; Elbayomy, Mohamed S. (Salehan Institute of Higher Education, 2025)
Cable-stayed bridges exhibit exceptional vulnerability to seismic excitation, particularly under combined vertical and horizontal ground motions in tectonically active regions. This study characterizes the seismic fragility of cable-stayed bridge towers using comprehensive probabilistic assessment methodologies. The framework integrates fragility curve development and Monte Carlo simulation, employing 30 earthquake ground motion records to construct robust statistical models of structural response. Fragility functions quantify the probability of exceeding predefined damage states across varying seismic intensity measures, while Monte Carlo analyses capture the stochastic nature of behavior and highlight response clustering around mean performance levels for distinct classifications. The findings reveal pronounced structural vulnerabilities within cable-stayed bridge systems, shaped by both epistemic and aleatory uncertainties that may lead to progressive collapse under extreme seismic events. Computational results indicate that although responses converge statistically around expected values, considerable scatter persists across limit states. For instance, at Sa(T1) = 1.0 g, exceedance probabilities diverge significantly: OP is almost certain (>99.9%), IO reaches 86.5%, DC 46.9%, and CP only 10.9%. Under more severe shaking (2.0 g), DC exceedance exceeds 98%, while CP remains 31%, illustrating substantial variability in fragility across thresholds. These results underscore the urgent need for improved seismic design philosophies in cable-stayed infrastructure within hazardous environments. The research advances bridge engineering practice by clarifying fundamental vulnerability mechanisms and guiding the development of innovative material systems, retrofit strategies, and structural health monitoring protocols aimed at enhancing seismic resilience.